Ternary positive electrode material and preparation method thereof

By using the phosphate coating of lithium zirconium titanium on the ternary positive electrode material, the problems of electrolyte corrosion and insufficient conductivity are solved, the circulation and power performance of lithium-ion batteries are improved, and the stability and lithium are achieved. Ion transfer efficiency.

CN119306196APending Publication Date: 2025-01-14HEFEI GUOXUAN HIGH TECH POWER ENERGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411380172.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2025-01-14

AI Technical Summary

Technical Problem

Nickel-rich ternary layered transition metal oxides increase internal resistance due to electrolyte corrosion and solid electrolyte membrane formation in lithium-ion batteries, limiting their commercial application, and existing inorganic non-metal oxide coating materials conduct electricity Inadequate sexuality affects the transmission of lithium ions.

Method used

Using lithium zirconium titanium phosphate as the coating layer, micron-level coating powder is prepared by ultrasonic dissolution and ultrasonic atomization technology, and ball milling and sintering with the ternary positive electrode material to form good conductivity and physical and chemical stability. cladding.

Benefits of technology

It effectively reduces the side reaction between the positive electrode material and the electrolyte, improves the circulation and power performance of lithium-ion batteries, and enhances the stability of the material and the transmission efficiency of lithium ions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005069702550000051
    Figure BDA0005069702550000051
Patent Text Reader

Abstract

The invention discloses a ternary positive electrode material and a preparation method thereof. The preparation method comprises the following steps: S1, adding a titanium source, a zirconium source and a lithium source into water, and dissolving to obtain a coating layer solution; s2, performing ultrasonic atomization on the coating layer solution to obtain micron-level liquid drops, and then passing through a high-temperature tube furnace to obtain coating layer powder; and S3, ball-milling the coating layer powder, mixing the ball-milled coating layer powder with a ternary positive electrode material, and sintering to obtain the ternary positive electrode material. The coating layer of the ternary positive electrode material is phosphate of lithium zirconium titanium, and the coating layer has good physical and chemical stability, so that the physical and chemical stability of the surface of the material can be effectively improved, and side reaction of an electrolyte and the positive electrode material is effectively reduced. The ternary positive electrode material prepared by the method provided by the invention has excellent cycle performance while having good gram capacity. And the coating layer of the ternary positive electrode material is a good lithium ion conductor, so that the diffusion of lithium ions can be promoted, and the power performance of the material is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a ternary positive electrode material and a preparation method thereof, belonging to the technical field of lithium ion batteries. Background Art

[0002] In recent years, with the demand for high energy density batteries, batteries have become thinner and lighter. Nickel (Ni)-rich ternary layered transition metal oxides (LiNi x Co y M 1-x-y O2, M=Mn or Al) has become a hot topic of research due to its superior energy density and low cost. However, the application of Ni-rich ternary layered transition metal oxides mainly faces the following problems: (1) The erosion of the electrolyte causes the dissolution of part of the transition metal in the material; (2) After the decomposition of the electrolyte at the positive electrode, a solid electrolyte (CEI) film will be formed, resulting in an increase in internal resistance. It is precisely because of the existence of these defects that the commercial application of Ni-rich ternary layered transition metal oxides is subject to certain restrictions.

[0003] In order to solve the above problems, coating is a very effective means. By coating a layer of inorganic metal oxide on the surface of the ternary positive electrode material, the side reaction between the material and the electrolyte can be effectively avoided, thereby enhancing the stability of the material and improving the cycle performance of the battery. At the same time, if the coating material has good conductivity, it can effectively improve the transmission of lithium ions, thereby improving the power performance of the positive electrode material.

[0004] At present, the main electrolyte lithium salt in lithium-ion batteries is lithium hexafluorophosphate (LiPF6). LiPF6 has poor thermal stability and is easily hydrolyzed with water to generate hydrogen fluoride (HF). HF will corrode the positive electrode material, dissolve the transition metal ions in the material, cause the crystal phase change, and deteriorate the battery performance. By coating a layer of inorganic non-metallic oxide on the surface of the ternary layered transition metal oxide material, the reaction between the electrolyte and the electrolyte can be effectively reduced, thereby improving the stability of lithium-ion batteries in the cycle.

[0005] At present, inorganic non-metallic oxides, fluorides, phosphates, etc. are mainly used, such as silicon dioxide (SiO2), cobalt oxide (Co3O4), molybdenum oxide (MoO3), zirconium oxide (ZrO2), zinc oxide (ZnO), aluminum oxide (Al2O3), aluminum fluoride (AlF3), manganese phosphate [Mn3(PO4)2], etc. as coating materials for ternary layered transition metal oxides. Although these materials can well protect the positive electrode material from being corroded by the electrolyte, most of them are not conductive, which to some extent affects the Li + Transport on the surface of the positive electrode material, thus affecting the performance of the battery. Summary of the invention

[0006] The purpose of the present invention is to provide a high-stability conductive coating layer coated with a high-power long-cycle ternary positive electrode material, which can effectively reduce the side reaction between the surface of the positive electrode material and the electrolyte, and greatly improve the cycle performance of the battery. At the same time, compared with traditional inorganic metal oxides, fluorides and phosphates, the coating layer of the present invention has good conductivity, and the coating can well promote Li + transmission, improving the rate performance of lithium-ion batteries.

[0007] The method for preparing the ternary positive electrode material provided by the present invention comprises the following steps:

[0008] S1, adding a titanium source, a zirconium source and a lithium source into water, and dissolving them to obtain a coating solution;

[0009] S2, the coating solution is subjected to ultrasonic atomization to obtain micron-sized droplets, and then passed through a high-temperature tube furnace to obtain a coating powder;

[0010] S3. The coating layer powder is ball-milled and mixed with the ternary positive electrode material, and then sintered to obtain the coating layer powder.

[0011] In the above preparation method, in step S1, the titanium source is an organic compound of titanium, the zirconium source is an inorganic salt of zirconium, and the lithium source is a phosphate compound of lithium;

[0012] The molar ratio of the lithium source, the titanium source and the zirconium source is 1:0.5-1.5:1.5-0.5.

[0013] The coating layer in the ternary positive electrode material of the present invention is lithium zirconium titanium phosphate, which has good physical and chemical stability.

[0014] In the above preparation method, in step S1, the coating layer solution is obtained by ultrasonic dissolution, and the ultrasonic conditions are as follows:

[0015] The ultrasonic frequency is 50-100 Hz, and the ultrasonic time is 1-4 hours.

[0016] In the above preparation method, in step S2, the conditions of the ultrasonic atomization are as follows:

[0017] Ultrasonic frequency is 1.5-2MHz;

[0018] Using compressed air as a carrier to make the micron-sized droplets pass through the high-temperature tube furnace;

[0019] The gas flow rate of the compressed air is 25-40L / min;

[0020] The temperature of the high temperature tube furnace is 800-950°C.

[0021] In the above preparation method, in step S3, zirconia balls are used for ball milling, the rotation speed is 500-800 rpm, the ball milling time is 2-4 hours, and the ball-to-material ratio is 1:1-3:1;

[0022] The particle size of the coating layer powder after ball milling is: 0.3≤D50≤0.5um.

[0023] In the above preparation method, in step S3, the coating layer powder is mixed with the ternary positive electrode material using alumina balls, the ball-to-material ratio is 1:1-3:1, and the mixing time is 3-5 hours.

[0024] In the above preparation method, in step S3, the chemical formula of the ternary positive electrode material is LiNi x Co y Mn z O2, 0.3 <x<1,0<y<0.4,0<z<1,x+y+z=1。

[0025] In the above preparation method, in step S3, the sintering conditions are as follows:

[0026] The atmosphere is compressed air or oxygen, the sintering temperature is 500-700°C, and the sintering time is 3-8h.

[0027] The coating layer of the ternary positive electrode material provided by the present invention is a phosphate of lithium zirconium titanium. Since the coating layer has good physicochemical stability, it can effectively improve the physicochemical stability of the material surface and effectively reduce the occurrence of side reactions between the electrolyte and the positive electrode material. At the same time, by ultrasonic atomization, micron-level coating droplets are obtained, which can greatly shorten the subsequent reaction time and improve production capacity. The ternary positive electrode material prepared by the method of the present invention has good gram capacity and excellent cycle performance. In addition, the coating layer of the ternary positive electrode material of the present invention is a good lithium ion conductor, which can promote the diffusion of lithium ions and improve the power performance of the material. DETAILED DESCRIPTION

[0028] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.

[0029] Unless otherwise specified, the materials and reagents used in the following examples are all commercially available.

[0030] Embodiment 1:

[0031] (1) 1.66 g, 2.1 g and 0.51 g of Ti(C4H9O)4, Zr(NO3)4·5H2O and LiH2PO4 were added to deionized water and ultrasonicated in an ultrasonic device at a frequency of 60 Hz for 1 h. Then, a coating layer raw material solution was obtained. The molar ratio of the lithium source, the titanium source and the zirconium source was 1:1:1.

[0032] (2) The coating layer raw material liquid obtained in step (1) is passed through an ultrasonic atomization device and transported to a tube furnace using compressed air as a carrier, with an ultrasonic frequency of 1.7 MHz, an air flow rate of 30 L / min, and a tube furnace temperature of 900° C. Then, a coating layer solid powder is obtained.

[0033] (3) The solid powder obtained in step (2) was added to a ball mill, and zirconium oxide balls were added according to a ball-to-material ratio of 2:1, and ball milling was performed at a speed of 600 rpm for 3 hours. Then, a coating layer solid powder was obtained after ball milling, and the particle size was 0.3 ≤ D50 ≤ 0.5 um.

[0034] (4) Add the ball-milled coating layer powder obtained in step (3) into a mixing tank, add 1 kg of ternary positive electrode material, add alumina balls and mix, wherein the amount of alumina balls added is 500 g, and the mixing time is 3 h. Then, a mixed ternary positive electrode material is obtained.

[0035] (5) Put the mixed ternary cathode material obtained in step (4) into a dry pot and then into a muffle furnace, introduce oxygen gas, set the heating parameters, heat to 700°C at a heating rate of 2°C / min, and keep warm for 5 hours. After sieving, the NCM cathode material with a uniform coating layer can be obtained.

[0036] Embodiment 2:

[0037] (1) 3.32 g, 4.2 g and 1.02 g of Ti(C4H9O)4, Zr(NO3)4·5H2O and LiH2PO4 were added to ethanol and ultrasonicated in an ultrasonic device at a frequency of 60 Hz for 1 h to obtain a coating layer raw material solution.

[0038] (2) The coating layer raw material liquid obtained in step (1) is passed through an ultrasonic atomization device and transported to a tube furnace using compressed air as a carrier, with an ultrasonic frequency of 1.7 MHz, an air flow rate of 30 L / min, and a tube furnace temperature of 900° C. Then, a coating layer solid powder is obtained.

[0039] (3) The solid powder obtained in step (2) was added to a ball mill, and zirconium oxide balls were added according to a ball-to-material ratio of 2:1, and ball milling was performed at a speed of 600 rpm for 3 hours. Then, a coating layer solid powder was obtained after ball milling, and the particle size was 0.3 ≤ D50 ≤ 0.5 um.

[0040] (4) Add the ball-milled coating layer powder obtained in step (3) into a mixing tank, add 1 kg of ternary positive electrode material, add alumina balls and mix, wherein the amount of alumina balls added is 500 g, and the mixing time is 3 h. Then, a mixed ternary positive electrode material is obtained.

[0041] (5) Put the mixed ternary cathode material obtained in step (4) into a dry pot and then into a muffle furnace, introduce oxygen gas, set the heating parameters, heat to 700°C at a heating rate of 2°C / min, and keep warm for 5 hours. After sieving, the NCM cathode material with a uniform coating layer can be obtained.

[0042] Embodiment 3:

[0043] (1) 4.98 g, 6.3 g and 1.53 g of Ti(C4H9O)4, Zr(NO3)4·5H2O and LiH2PO4 were added to ethanol and ultrasonicated in an ultrasonic device at a frequency of 60 Hz for 1 h. Then, a coating layer raw material solution was obtained.

[0044] (2) The coating liquid obtained in step (1) is passed through an ultrasonic atomization device and transported to a tube furnace using compressed air as a carrier, with an ultrasonic frequency of 1.7 MHz, an air flow rate of 30 L / min, and a tube furnace temperature of 900° C. Then, a coating layer solid powder is obtained.

[0045] (3) The solid powder obtained in step (2) was added to a ball mill, and zirconium oxide balls were added according to a ball-to-material ratio of 2:1, and ball milling was performed at a speed of 600 rpm for 3 hours. Then, a coating layer solid powder was obtained after ball milling, and the particle size was 0.3 ≤ D50 ≤ 0.5 um.

[0046] (4) Add the ball-milled coating layer powder obtained in step (3) into a mixing tank, add 1 kg of ternary positive electrode material, add alumina balls and mix, wherein the amount of alumina balls added is 500 g, and the mixing time is 3 h. Then, a mixed ternary positive electrode material is obtained.

[0047] (5) Put the mixed ternary cathode material obtained in step (4) into a dry pot and then into a muffle furnace, introduce oxygen gas, set the heating parameters, heat to 700°C at a heating rate of 2°C / min, and keep warm for 5 hours. After sieving, the NCM cathode material with a uniform coating layer can be obtained.

[0048] Embodiment 4:

[0049] (1) 3 g, 3.79 g and 0.92 g of Ti(C4H9O)4, Zr(NO3)4·5H2O and LiH2PO4 were added to ethanol and ultrasonicated in an ultrasonic device at a frequency of 60 Hz for 1 h. Then, a coating layer raw material solution was obtained.

[0050] (2) The coating liquid obtained in step (1) is passed through an ultrasonic atomization device and transported to a tube furnace using compressed air as a carrier, with an ultrasonic frequency of 1.7 MHz, an air flow rate of 30 L / min, and a tube furnace temperature of 900° C. Then, a coating layer solid powder is obtained.

[0051] (3) The solid powder obtained in step (2) was added to a ball mill, and zirconium oxide balls were added according to a ball-to-material ratio of 2:1, and ball milling was performed at a speed of 600 rpm for 3 hours. Then, a coating layer solid powder was obtained after ball milling, and the particle size was 0.3 ≤ D50 ≤ 0.5 um.

[0052] (4) Add the ball-milled coating layer powder obtained in step (3) into a mixing tank, add 1 kg of ternary positive electrode material, add alumina balls and mix, wherein the amount of alumina balls added is 500 g, and the mixing time is 3 h. Then, a mixed ternary positive electrode material is obtained.

[0053] (5) Put the mixed ternary cathode material obtained in step (4) into a dry pot and then into a muffle furnace, introduce oxygen gas, set the heating parameters, heat to 700°C at a heating rate of 2°C / min, and keep warm for 5 hours. After sieving, the NCM cathode material with a uniform coating layer can be obtained.

[0054] Comparative Example 1:

[0055] (1) 7000 g of NCM6506 precursor and 3040 g of Li2CO3 were mixed evenly using a high-speed mixer, and then the mixed materials were placed in a sagger and shaken to compact, and then the materials were cut into cubes of the same size;

[0056] (2) Place the sagger containing the material in a muffle furnace and heat it to 880°C at a heating rate of 2°C / min and keep it warm for 15 hours. At the same time, compressed air is continuously introduced during the entire reaction process with a gas flow rate of 0.6m 3 / h.

[0057] (3) The material sintered in step (2) was crushed and sieved, and then placed in a muffle furnace, oxygen was introduced as gas, and the heating parameters were set to heat the material to 700°C at a heating rate of 2°C / min, and kept warm for 3 hours. After that, the material was sieved to obtain an uncoated NCM positive electrode comparison sample material.

[0058] The positive electrode materials, conductive carbon black, and PVDF obtained in each embodiment and comparative example were mixed in a ratio of 90:5:5, and NMP was used as a solvent to mix them evenly, and then they were evenly coated on aluminum foil to make button batteries to test their electrochemical properties. The test was carried out at room temperature 25°C, and the first four weeks were charged and discharged at 0.2C / 0.2C, 0.33C / 0.33C, 1C / 1C, and 0.2C / 0.2C, respectively, and then at 1C / 1C for 50 cycles. The button battery performance data is shown in Table 1.

[0059] Table 1 Electrochemical performance of button cells tested

[0060]

[0061] Compared with the comparative example, it can be seen that the material's capacity and cycle performance are significantly improved by the coating of the coating layer, and the power performance is also improved to a certain extent. It can be seen from the comparative example that as the coating layer becomes thicker, although the cycle performance tends to increase, the capacity and power performance show a trend of first increasing and then decreasing, which is related to the coating layer not having reactivity, so choosing a suitable coating amount can take into account various performances.

Claims

1. A method for preparing a ternary positive electrode material, comprising the following steps: S1, adding a titanium source, a zirconium source and a lithium source into water, and dissolving them to obtain a coating solution; S2, the coating layer solution is subjected to ultrasonic atomization to obtain micron-sized droplets, and then passed through a high-temperature tube furnace to obtain a coating layer powder; S3. The coating layer powder is ball-milled and mixed with the ternary positive electrode material, and then sintered to obtain the coating layer powder.

2. The preparation method according to claim 1, characterized in that: In step S1, the titanium source is an organic compound of titanium, the zirconium source is an inorganic salt of zirconium, and the lithium source is a phosphate compound of lithium; The molar ratio of the lithium source, the titanium source and the zirconium source is 1:0.5-1.5:1.5-0.

5.

3. The preparation method according to claim 1 or 2, characterized in that: In step S1, the coating layer solution is obtained by ultrasonic dissolution, and the ultrasonic conditions are as follows: The ultrasonic frequency is 50-100 Hz, and the ultrasonic time is 1-4 hours.

4. The preparation method according to claim 1 or 2, characterized in that: In step S2, the conditions of the ultrasonic atomization are as follows: Ultrasonic frequency is 1.5-2MHz; Using compressed air as a carrier, the micron-sized droplets are passed through the high-temperature tube furnace; The gas flow rate of the compressed air is 25-40L / min; The temperature of the high temperature tube furnace is 800-950°C.

5. The preparation method according to claim 1 or 2, characterized in that: In step S3, zirconia balls are used for ball milling, the rotation speed is 500-800 rpm, the ball milling time is 2-4 hours, and the ball-to-material ratio is 1:1-3:1; The particle size of the coating layer powder after ball milling is: 0.3≤D50≤0.5um.

6. The preparation method according to claim 1 or 2, characterized in that: In step S3, the coating layer powder is mixed with the ternary positive electrode material using alumina balls, the ball-to-material ratio is 1:1-3:1, and the mixing time is 3-5 hours.

7. The preparation method according to claim 1 or 2, characterized in that: In step S3, the chemical formula of the ternary cathode material is LiNi x Co y Mn z O2, 0.3 <x<1,0<y<0.4,0<z<1,x+y+z=1。 8. The preparation method according to claim 1 or 2, characterized in that: In step S3, the sintering conditions are as follows: The atmosphere is compressed air or oxygen, the sintering temperature is 500-700°C, and the sintering time is 3-8h.

9. The ternary positive electrode material prepared by the method according to any one of claims 1 to 8.